2020
DOI: 10.1109/access.2020.3005235
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Real-Time Multi-Core Assignment Scheme for Asymmetric Multi-Core Mobile Devices

Abstract: The big.LITTLE architecture has been extensively integrated into smart mobile devices for better performance and higher energy efficiency. However, the desired energy savings obtained by the big.LITTLE architecture is not sufficiently achieved because the LITTLE cores are not fully utilized while running real-time user applications. In this study, an energy efficient big.LITTLE core assignment algorithm is proposed to reduce the energy consumption of the mobile device by utilizing the LITTLE core as much as po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…There are four basic techniques for minimizing power dissipation in embedded electronic systems: voltage scaling, frequency scaling, power gating, and clock gating. As is well known, many theoretical considerations, as well as practical experiments, have shown that the energy consumed by electronic circuits strongly depends on the operating frequency [2,8,9,[15][16][17][18].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…There are four basic techniques for minimizing power dissipation in embedded electronic systems: voltage scaling, frequency scaling, power gating, and clock gating. As is well known, many theoretical considerations, as well as practical experiments, have shown that the energy consumed by electronic circuits strongly depends on the operating frequency [2,8,9,[15][16][17][18].…”
Section: Related Workmentioning
confidence: 99%
“…Usually, it is a trade-off between energy and system performance [9]. Kim et al [15] presents experiments on ARM's LITTLE real-time architecture that show a strong correlation between the energy and the system performance; its authors try to accommodate real-time task deadlines, working in mobile applications, into the system throughput. Li has made some interesting theoretical considerations in his paper [8] regarding energy and time-constrained task scheduling on multiprocessor computers.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of using different styles of coding for balancing between performance and energy consumption of the processing cores is presented in [11]. A core allocation technique to lower the energy usage of mobile devices by engaging the LITTLE cores to a maximum extent and ensuring the performance of the device is proposed in [12]. The execution time of complex programs can be minimized and thus the performance of the applications can be improved by the use of today's high-performance computing systems employing multi-core processors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scheduling typed DAG tasks with real-time constraints on heterogeneous multicore platforms is an emerging research topic. Most of the prior work [3], [9], [16], [18] focuses on scheduling un-typed real-time DAG tasks on heterogeneous platforms, and proposes methods for determining the core type each code segment (i.e., each vertex in a DAG) should be executed on. For typed DAG tasks, Han et al [13] • C.-C. Lin, J. Shi, N. Ueter, M. Günzel and J.-J.…”
Section: Introductionmentioning
confidence: 99%